Mutational Analysis of EZH2 in the Germinal Centre Type of Diffuse Large B Cell Lymphoma - Abbas, Farah Fatima; Bari, Muhammad Furqan; Mughal, Muhammad Nouman; Khan, Bilal Ahmed; Khan, Nehad; Kamil, Saba; Razzaq, Abdul; Kamil, Noor (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To determine the Frequency of Germinal Center B (GCB) type Diffuse Large B Cell Lymphoma (DLBCL) in Karachi, Pakistan, and to screen the DLBCL patients for EZH2 mutation. METHODOLOGY: A cross-sectional study was conducted on DLBCL patients, and IHC analysis, PCR, and sequencing of the EZH2 gene were used. This study was conducted from August 2016 to July 2020. Surgical specimens received in the histopathology section of DDRRL centrally and from different collection units throughout Sindh having been diagnosed with DLBCL were collected. Three markers (CD10, BCL6, and MUM1) were used for subtyping. DNA was manually extracted from the FFPE Blocks of DLBCL cases using phenol: chloroform: isopropanol alcohol. Polymerase chain reaction (PCR) was performed, and samples were sent from Dow University to Korea (Macrogen) for sequencing. The amplified product was 189bp. Primers were used for EZH2 to flank the region containing the tyrosine domain on exon 16 and exon 18. RESULTS: Out of 116 cases, 60.3% and 39.7% were male and female, respectively. The mean age was 49.73±16.38 years. The mean survival duration of cases diagnosed with GCB was 8.21±7.39 months. Polymorphism of EZH2 mutation (Tyr 701 Asn) was found to be positive in GCB-DLBCL for three samples (16.6%). CONCLUSION: In the current study, Sanger sequencing was used to detect any mutation in the coding region of EZH2, and a unique mutation was reported (Tyr701Asn).